A trama da vida - Menezes Filho, Abel (2010)
On the basis of the knowledges are fragmented and placed in watertight compartments, this thesis proposes that art, by its transdisciplinary characteristics, may contribute to bridging, to make reconnections, entanglement. The complex thinking is the inspiration and literature was the method chosen to shows this possible dialogue. The narrative is woven by four characters, two women and two men, who proposes to write a collective book. The characters lives in different cities and began the dialogue by e-mails. The model chosen was the caduceus of Hermes, a bat where two snakes interwine , in seven vertexes. Unfolded in the plane there are three narratives, parallel, autonomous and simultaneously intertwined. The side snakes is the form I found to dialogue with the authors with more fluidity and break with the usual understanding of notes, which support or complement the main text, often by rote. Caduceu s doublé helix has resonances with the genetic code, that from four letters, combined in pairs, in different extents, create all forms of life. Although any of the four characters have their predominant thematic fields, the knowledges exchange became possible and the model suited as well